FRI0180 Multiple sclerosis risk-alleles study in patients with demyelinating side effects on anti tnf alpha therapy. (15th June 2017) - Bitoun, S; Verstuyft, C; Miceli-Richard, C; Berthelot, J-M; Richez, C; Cauquil, C; Sordet, C; Melac-Ducamp, S; Gossec, L; Beatrice, B; Dernis, E; Houvenagel, E; et al.
Abstract : Background: Tumor Necrosis Factor alpha (TNFα) is a key cytokine in inflammatory rheumatic diseases. TNF inhibitors (TNFi) has revolutionized treatment of rheumatic diseases, but may cause flares of multiple sclerosis (MS). Two Single Nucleotide Polymorphisms, (SNPs) rs1800693 and rs4149584, located within TNF receptor superfamilly 1 ( TNFRSF1A ) locus have been shown to increase the risk of developing MS [1]. The rs1800693*G allele leads to a dysfunctional TNFα soluble receptor that inhibits TNFα signaling while rs4149584 is involved in TNF receptor associated periodic syndrome. Objectives: The aim of this study was to look for a possible the association between TNFRSF1A polymorphisms and demyelinating complications occurring during TNFi therapy. Methods: Patients who presented with a demyelinating disorder (central or peripheral involvement) while treated with TNFi (cases), were recruited between March 2013 and December 2015, through the physicians involved in the CRI ("Club Rhumatismes et Inflammation") a nationwide network of the French Society of Rheumatology. Rheumatoid arthritis patients treated with TNFi, from the French ReAct cohort, and who did not develop demyelinating complication constituted the control population (n=294). The frequency of rs1800693 and rs4149584 TNFRSF1A SNPs were compared between cases and controls. Results: Twenty-four cases with demyelinating disorders, recruited from 11 centers with a median age of 39.7 years (range 30.4–75.8); of which 16 (67%) were females were included in the study. Neurological symptoms occurred after a median of 18.3 (1–66) months of anti TNFi; 15 (62.5%) had central neurologic involvement and 9 (37.5%) had peripheral involvement. The median follow-up was 26 (4–54) Months. No significant difference in the frequency of the rs1800693 MS risk-alleles (39, 5% for cases vs 38, 6% for controls) was observed. Similarly no difference was observed between cases (2%) and controls (4%) for rs4149584. Conclusions: This study was unable to show an association between MS-associated SNPs within TNFRSF1A locus and the occurrence of demyelination while taking TNFi, suggesting that demyelination might be linked to other genetic factors or other pathways. References: De Jager PL, Jia X, Wang J, et al. Meta-analysis of genome scans and replication identify CD6, IRF8 and TNFRSF1A as new multiple sclerosis susceptibility loci. Nat Genet 2009;41:776–82. doi:10.1038/ng.401. Disclosure of Interest: None declared